ENRICHING THE ISLAMIC EDUCATION MATERIAL TO INCREASE CHILD AFFECTIVE USING TYPES OF LEARNING OF ROBERT M. GAGNE - Apriyani Lestari Kudadiri (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2018)
Abstract: This study analyzes the obstacles or difficulties in teaching Islamic religion, especially in Kindergarten. The goal is to find out what are the obstacles and difficulties for teachers in delivering Islamic teachings to early childhood. The data are collected from are two Kindergarten i.e. Mashitoh Kentagen and Hidayatul Qur'an. The researcher analyzes the difficulties experienced by the teacher along with efforts to overcome them. The method used in this data collection is the method of observation, interviews, and documentation. The results of this study contributed in the form of material deepening models that can answer the problems of Core Competencies (Kompetensi Inti-KI) 1 and 2. This deepening model of Islamic Education material is seen from eight types of learning proposed by Robert M. Gagne. The eight types are signal learning, stimulus-response learning, chaining (chain sequence), verbal association, discrimination learning (learning to distinguish), concept learning, rule learning and problem-solving.